Improved Field Size Bounds for Higher Order MDS Codes - Brakensiek, Joshua; Dhar, Manik; Gopi, Sivakanth (ISIT 2023, 2022)
Higher order MDS codes are an interesting generalization of MDS codes recently introduced by Brakensiek, Gopi and Makam (IEEE Trans. Inf. Theory 2022). In this work, we give new upper and lower bounds on the field size required for higher order MDS codes.